2020
DOI: 10.1289/ehp6047
|View full text |Cite
|
Sign up to set email alerts
|

Phthalate and Bisphenol Exposure during Pregnancy and Offspring Nonverbal IQ

Abstract: Background: Prenatal exposures to phthalates and bisphenols are associated with impaired brain development in animals. However, epidemiological studies investigating the association between prenatal phthalate or bisphenol exposure and cognition have produced mixed findings and mostly had modest sample sizes and measured the exposure during the third trimester. Objective: We examined the association between pregnancy maternal urinary biomarkers of phthalate or bisphenol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 135 publications
(167 reference statements)
1
12
1
Order By: Relevance
“…The strongest contributors to the overall negative mixture association on nonverbal IQ were MECPP, MCPP, monoisobutyl phthalate (MiBP), and dimethylthiophosphate (DMTP). In a previous work where we used the same population to investigate phthalate metabolites exposure in association with nonverbal IQ using separate regression analyses, we showed that the averaged concentrations of MCPP and PA across pregnancy had the largest association with nonverbal IQ with larger effect estimates as compared to the estimates observed in this study . These different findings indicate that by modeling co-occurring chemical exposures, exposure biomarkers combinations playing a substantial role in the association with a certain outcome might be identified, that are missed in single regression models that do not adjust for or take into account coexposure effects.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The strongest contributors to the overall negative mixture association on nonverbal IQ were MECPP, MCPP, monoisobutyl phthalate (MiBP), and dimethylthiophosphate (DMTP). In a previous work where we used the same population to investigate phthalate metabolites exposure in association with nonverbal IQ using separate regression analyses, we showed that the averaged concentrations of MCPP and PA across pregnancy had the largest association with nonverbal IQ with larger effect estimates as compared to the estimates observed in this study . These different findings indicate that by modeling co-occurring chemical exposures, exposure biomarkers combinations playing a substantial role in the association with a certain outcome might be identified, that are missed in single regression models that do not adjust for or take into account coexposure effects.…”
Section: Discussioncontrasting
confidence: 56%
“…In real world situations, fetal exposure to these nonpersistent chemicals co-occurs in exposure combinations. Except for a small number of studies, the majority of studies investigating the association between prenatal exposure to these chemicals and neurodevelopment in children, including our previous work, have applied single exposure models, which have important limitations . For example, co-occurring chemical exposures may join additively to produce larger effects which cannot be investigated. Further, single exposure analyses may be biased if potential cochemical confounding exists.…”
Section: Introductionmentioning
confidence: 99%
“…We selected the LOD cut-off of 20% because with this cut-off we were able to include the maximum number of participants in the analyses with adequate variability in the bisphenol data to detect associations. This approach is in line with previous studies in the field (Philips et al, 2018 ; Sol et al, 2020 ; van den Dries et al, 2020 ). Bisphenols A, S and F met those inclusion criteria (Supplementary Table S1).…”
Section: Methodssupporting
confidence: 89%
“…Interestingly, the inverse associations between blood exposure biomarkers and the AC z-score were stronger for first-trimester blood THM concentrations, suggesting that early pregnancy may be a potentially vulnerable window. This is biologically plausible given that early pregnancy is crucial for the development of the placenta and fetal organs, , which is sensitive to environmental toxicants. Numerous epidemiological studies have found that exposure to certain environmental pollutants during the first trimester was associated with reduced fetal growth parameters. Our results also showed that THM exposures can impair fetal growth in the second trimester, possibly via altering hormone regulation, disrupting placental growth and/or triggering the oxidative stress response. , Early-onset growth retardation is a significant concern given its association with various adverse health outcomes in children and adults. , However, more mechanistic studies are needed to clarify our observed trimester-specific associations.…”
Section: Discussionmentioning
confidence: 56%